2018
DOI: 10.1590/1807-3107bor-2018.vol32.0127
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control among individuals with different pain conditions

Abstract: The objective of this study was to evaluate the psychometric properties of the Multidimensional Health Locus of Control-Form C (MHLC-C) scale applied to a sample of adult Brazilian patients with different pain conditions. The scores were then identified and compared on each of the subscales and profiles regarding locus of control. The sample consisted of 1,149 adult individuals (79% women; mean age: 36.6 years) of which 334 reported not feeling pain in the prior 24 hours, 386 reported pain in the prior three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Regarding the main goal of this study, four factors comprising 18 items were used confirmed in CFA with 13 items, after the exclusion of one item related to "Chance" and four items related to "Internal". Other research has verified various item numbers in CFA: 18 items among pregnant women [28], 18 items among patients with rheumatoid arthritis [42], 18 items across three factors, combining the "Doctors" and "Others People" subscales into one among patients with various health conditions [43], 18 items across three factors, combining the "Doctors" and "Others People" subscales into "Powerful Other People" among early pregnancy women [44], 17 items (omitted I18 related to the "Internal" factor) among both genders and focused on type 2 diabetes patients [30], and 16 items, with two pertaining to "Chance" [31]. These discrepancies could stem from cultural, environmental, situational, and demographic differences [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the main goal of this study, four factors comprising 18 items were used confirmed in CFA with 13 items, after the exclusion of one item related to "Chance" and four items related to "Internal". Other research has verified various item numbers in CFA: 18 items among pregnant women [28], 18 items among patients with rheumatoid arthritis [42], 18 items across three factors, combining the "Doctors" and "Others People" subscales into one among patients with various health conditions [43], 18 items across three factors, combining the "Doctors" and "Others People" subscales into "Powerful Other People" among early pregnancy women [44], 17 items (omitted I18 related to the "Internal" factor) among both genders and focused on type 2 diabetes patients [30], and 16 items, with two pertaining to "Chance" [31]. These discrepancies could stem from cultural, environmental, situational, and demographic differences [23].…”
Section: Discussionmentioning
confidence: 99%
“…(2) there appears to be a lack of studies evaluating the psychometric properties of MHLC scales specifically for menopausal women, and (3) only a limited number of studies have validated the psychometric properties of the MHLC-C, including studies among pregnant women, type 2 diabetic patients, and individuals with various pain conditions [28,30,31]. As a result, there is currently a lack of a dedicated tool to evaluate menopausal women's perceptions of HLC.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, awareness of the limited duration of the condition predisposes the person to greater tolerance and forbearance, limiting the intensity of anticipatory fear associated with such conditions. However, in the literature, the role of internal locus of control in mitigating the experience of mild pain is reported in several studies ( Bonafé et al, 2018 ; Löffler et al, 2018 ; Musich et al, 2020 ; González-Roldán et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Internal locus of control is defined as the degree to which people believe outcomes are the function of their own behaviors. This is in contrast to an external locus of control, which is defined as the belief that the outcomes can be attributed to others (or external factors such as luck) but not their own behaviors ( Bonafé et al, 2018 ; Rotter, 1990 ). Locus of control is also known as a psychological construct that heavily impacts individuals’ ability to cope with adversity ( Rotter, 1990 ).…”
Section: Sense Of Control and Chronic Painmentioning
confidence: 99%
“… Nazareth (2016) found that locus of control is significantly associated with pain outcomes as well as adjustment outcomes. For instance, individuals who endorsed an internal locus of control reported lesser degrees of psychological distress and had more positive chronic pain outcomes while individuals with an external locus of control reported increased disability, psychological distress, and no significant pain improvement during an inpatient chronic pain treatment program ( Bonafé et al, 2018 ; Heath et al, 2008 ; Lee et al, 2020 ; Zuercher-Huerlimann et al, 2019 ).…”
Section: Sense Of Control and Chronic Painmentioning
confidence: 99%